1985
DOI: 10.4039/ent1171523-12
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-DOSAGE TREATMENT OF A QUEBEC STREAM WITH BACILLUS THURINGIENSIS SEROVAR. ISRAELENSIS: EFFICACY AGAINST BLACK FLY LARVAE (DIPTERA: SIMULIIDAE) AND IMPACT ON NON-TARGET INSECTS

Abstract: A typical lake outlet of the Canadian Shield was treated for 15 min with a high dose (5.28 g/L s−1 of discharge) of Teknar®, a commercial formulation of Bacillus thuringiensis serovar. israelensis. Efficacy on Simuliidae larvae and impact on non-target aquatic insects of this stream were monitored using drift nets, counting plates, and artificial turf substrates along a 1000-m section downstream of the site of application. Compared with a 4-day pre-treatment average for 12-h sampling periods, drift of Simuliid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…This bacterial larvicide is recognized as highly selective for Nematocera, the taxonomic group of dipterans to which belong Culicidae, Simuliidae and Chironomidae. All the field studies showing effects of Bti on chironomids were carried out in controlled conditions (in situ enclosures or outdoor artificial ponds; Miura et al, 1980, Ali, 1981, Charbonneau et al, 1994, Liber et al, 1998, Pont et al, 1999, Russell et al, 2009, or in rivers where black fly larvae were controlled (Car and de Moor, 1984, Back et al, 1985, Merritt et al, 1989, Molloy, 1992, Palmer, 1993Jackson et al, 1994;MacCracken andMatthews, 1997, Jackson et al, 2002), with dosages of Bti much higher than those used for mosquito control. Stevens et al (2004) compared toxicity of a Bti commercial formulation (Vectobac WDG; 3000 UTI/mg) and a spore/crystal mixture against Chironomus tepperi larvae, considering chironomids as a pest for rice cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterial larvicide is recognized as highly selective for Nematocera, the taxonomic group of dipterans to which belong Culicidae, Simuliidae and Chironomidae. All the field studies showing effects of Bti on chironomids were carried out in controlled conditions (in situ enclosures or outdoor artificial ponds; Miura et al, 1980, Ali, 1981, Charbonneau et al, 1994, Liber et al, 1998, Pont et al, 1999, Russell et al, 2009, or in rivers where black fly larvae were controlled (Car and de Moor, 1984, Back et al, 1985, Merritt et al, 1989, Molloy, 1992, Palmer, 1993Jackson et al, 1994;MacCracken andMatthews, 1997, Jackson et al, 2002), with dosages of Bti much higher than those used for mosquito control. Stevens et al (2004) compared toxicity of a Bti commercial formulation (Vectobac WDG; 3000 UTI/mg) and a spore/crystal mixture against Chironomus tepperi larvae, considering chironomids as a pest for rice cultures.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the short carry observed with Bti formulations, Undeen and Colbo (1980) suggested that the large substrate-surface-area/volume ratio inherent to small streams resulted in rapid removal of Bti by stream¯ora and fauna. Back et al (1985) found after a high-dosag e treatment that periphyton-grazer s (Diptera: Blephariceridae) were poisoned by Bti (as seen by the destruction of the midgut in dead drifting larvae). These results indicated that the Bti crystals had been adsorbed by the algae growing on rocks.…”
Section: Fate Of Bti Toxic Activity In the Environmentmentioning
confidence: 99%
“…Even though Bti is known to be very eYcient against target organisms, literature tends to demonstrate that Bti applied in experimental`overdose' conditions can aVect some nontarget organisms (NTO) Back et al, 1985;Fortin et al, 1986;Charbonneau et al, 1994;Su & Mulla, 1999). This review will focus on the eVects of Bti on target as well as nontarge t organisms.…”
Section: Introductionmentioning
confidence: 96%
“…lentic freshwater: Norland & Mulla 1975, Hershey et al 1998; lotic freshwater: Car & de Moor 1984, Back et al 1985. Many laboratory studies have provided information on the specific responses of different taxa to Bti and/or smethoprene, with the majority of these studies recording no impacts when non-target insects were exposed to operational concentrations (see reviews by Glare & O'Callaghan 1998, Boisvert & Boisvert 2000.…”
Section: Introductionmentioning
confidence: 99%